Effects of tetrahydroprotoberberines on dopamine D2 receptors in ventral tegmental area of rat - Wang Ling-Ming; Zhang Xue-Xiang; Jin Guo-Zhang (Acta Pharmacologica Sinica; Vol 18, No 2 (March 1997): Acta Pharmacologica Sinica, 2016)
AIM: To compare the actions of tetrahydroprotoberberines (THPB) on dopamine (DA) D2 receptors in the ventral tegmental area (VTA) of rat. METHODS: Extracellular single unit recording technique was used in i.v. gallamine-paralyzed rats. RESULTS: Eleven THPB analogs tested completely attenuated the apomorphine (Apo, 20 micrograms.kg-1)-induced inhibition on VTA DA cell firing activity. The OH group on C2 at THPB was linked with the reversal of Apo-induced inhibition. Their reversal potencies (ED50, microgram.kg-1) for D2 receptors were: THPB-143 (5.6) > SPD (8.5) > Iso (17.0) > THP (33) > THB (48) > THPB-18 (66) > THPB-1 (179) > THPB-19 (408) > THPB-126 (510) > THPB-104 (1019) > THPB-10 (4815). CONCLUSION: Among these 11 THPB, the 2-hydroxyl-THPB (THPB-143) showed the strongest antagonistic action on D2 receptors.